PELATIHAN EARN MONEY MAKER FOR ANDROID UNTUK PENINGKATKAN PASSIVE INCOME BAGI WARGA KELURAHAN JATIREJO KECAMATAN GUNUNGPATI KOTA SEMARANG - Patricia Dhiana Paramita; Nurkholik Nurkholik (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2026)
This community service activity was conducted to implement the partnership between Universitas Pandanaran and the Gunungpati District administration in Semarang City. Specifically, the initiative aimed to shift residents' mindsets—encouraging them not to rely solely on formal employment for income but to also consider using Android-based smartphones to generate passive income. The activity was held in two sessions, on July 5 and July 12, 2026. Overall, the event proceeded successfully and received a positive response from the residents.